The Effect of Repetition on the Perceived Truth of Tobacco-Related Health Misinformation Among U.S. Adults - Morgan, Jennifer C.; Cappella, Joseph N. (Journal of health communication, 2023)
As concerns about the effects of health misinformation rise, understanding why misbeliefs are accepted is increasingly important. People believe repeated statements more than novel statements, an effect known as truth by repetition, however this has not been examined in the context of tobacco information. Misbeliefs about tobacco are rampant and novel facts about tobacco are viewed as less believable. This paper examines how repetition of true and false tobacco statements affects truth perceptions. We recruited an online sample of 1,436 U.S. adults in May 2021. In an exposure phase, each participant rated their interest in 30 randomly selected statements about tobacco products and general knowledge trivia, half of them true and half false. The study had a two (tobacco product) by two (familiarity of statement claim) between-subjects design and a two (statement truth) by two (statement repetition) within-subjects design. During the testing phase participants rated the truthfulness of 24 repeated statements and 24 unseen statements. Repetition of true and false tobacco statements increased their subjective truth (diff=.20, p < .001), and the effect was larger for false claims compared to true claims. This underscores the importance of strategies to inoculate people against misinformation and calls for interventions that can stop the repetition of newly generated false claims.